GERAKAN SOSIAL POLITIK BURUH STUDI TENTANG PERANAN FEDERASI SERIKAT PEKERJA METAL INDONESIA DALAM MEMPERJUANGKAN HAK POLITIK PENGUPAHAN DI KABUPATEN BEKASI - Febriantin, Kariena; Anggrayni , Irena (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
The aim of this research is to explore and evaluate the function of the Indonesian Metal Workers Union Federation in advocating for political rights concerning salaries in Bekasi Regency. This investigation draws on political process theory, which identifies three critical components for the effectiveness of social movements: organizational strength, cognitive liberation, and political opportunities (McAdam in Sukmana, 2016: 197-204). A qualitative method with a descriptive framework is employed for this study. The data drawn upon comprises both primary and secondary sources. Relevant techniques are utilized for data gathering. These techniques encompass observation, interviews, surveys, documentation, and a mix of these approaches. Informants are chosen using purposive sampling to ensure the researcher acquires the necessary information. The findings reveal that, firstly, from the standpoint of organizational strength, a sense of connection and mutual support among FSPMI members has developed. This is evident in the rising number of workers enrolling as FSPMI members and in efforts to enhance membership and formulate a collective strategy through regular discussions. Secondly, concerning cognitive liberation, FSPMI educates its members politically via discussions held between the central organization and unit leaders, while also consolidating efforts to improve communication and coordination, thus strengthening the ties between members and management. Lastly, in the context of political opportunities, attempts are made to engage with the ruling party and lobby the regent regarding wage adjustments. This advocacy occurs through tripartite negotiations involving the government, employers, and workers, along with bipartite negotiations aimed at addressing company-related issues through dialogue.